Strategi Pengembangan Sumberdaya Insani dalam Meningkatkan Kinerja Karyawan di BUMDES Tunas Abadi Desa Waru Kecamatan Lohbener Kabupaten Indramayu - Arwani Arwani (LPPM STAIS Dharma Indramayu, 2020)
Human Resources are the most important asset that every company has, because every activity and activity involves Human Resources. However, the ability and knowledge of Human Resources is basically limited, so a strategic concept is needed in managing Human Resources, one of which is through a Human Resources development strategy, by assessing the education and training aspects of employees. This research is descriptive qualitative in nature, trying to describe the research results as they are. Data collection techniques use observation, interviews and documentation. The data obtained is then processed in the form of words or text which is then put into the form of a description or narrative. The subjects in this research are the director, personnel department and employees of BUMDes Tunas Abadi Waru Lohbener Indramayu, while the objects of this research are all activities related to the Human Resources development strategy at BUMDes Tunas Abadi Waru Lohbener Indramayu. Based on the results of research conducted by the author regarding Human Resource Development Strategies in Improving Employee Performance at BUMDes Tunas Abadi Waru Lohbener Indramayu, it can be concluded that in order to increase employee abilities or potential, a Human Resource development strategy is needed, starting from the recruitment, selection, placement process. , training, career development, and Islamic guidance. Even though in its implementation there are still several obstacles, such as participants who have different educational backgrounds, expert and professional trainers are still relatively rare, facilities are still limited, and the curriculum presented in training activities is still not in line with the company's expectations, but BUMDes Tunas Abadi Waru Lohbener Indramayu, remain enthusiastic and continue to strive so that in the future efforts to develop Human Resources run better.